PENGARUH DANA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR PADA KAMPUNG KLAWAREN, DISTRIK WEMAK, KABUPATEN SORONG - Obed Mlik; Ade Andriani Renouw; Agnes Banea (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the influence of village funds on infrastructure development. The data analysis method used is quantitative descriptive analysis. significant test through (t-test), using simple linear regression and coefficient of determination (R2). The population in this study were 56 people from Klawaren Village, Wemak District, Sorong Regency. the sample amounted to 34 respondents. Primary data were obtained through interviews, questionnaires and documentation studies. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 9.824 + 0.592X the regression coefficient value of 0.592 means that every time there is a change and an addition of one percent in the village fund variable, the infrastructure development variable will increase by 0.592 if the village fund variable is zero, then infrastructure development has a value of 9,824. In the coefficient of determination test obtained R square 55.9%. meaning that village funds have an effect on infrastructure development by 55.9%. while the remaining 44.1% is influenced by other factors not analyzed in this study. The results of the t-test, where tcount 8,273 > from ttable 1.6939, it can be said that the village fund variable has a positive and significant effect on infrastructure development.